Comparison of the Law on Pronouncing Taklik Talak According to the Kedah Enactment and the Compilation of Islamic Law - Muhammad Farid bin Norazam; Muhammad Torik; Sandy Wijaya (Fakultas Syariah dan Hukum UIN Raden Fatah Palembang, 2025)
The pronouncement of taklik talak after the marriage contract is a well-known practice in Islamic family law traditions in Malaysia and Indonesia. However, its legal status is not uniform in the two countries. This study aims to analyze and compare the legal provisions for pronouncing taklik talak in marriage according to the Enakmen of the Islamic Family Law of Kedah State Number 7 of 2008 and Presidential Instruction Number 1 of 1991 concerning the Compilation of Islamic Law in Indonesia. This type of research is qualitative with a normative juridical approach and a comparative legal approach through a literature study of laws and regulations, official documents, and fiqh literature. The results show that in Malaysia (Kedah State), pronouncing taklik talak is an administrative obligation that must be carried out after the marriage contract; a husband who refuses to pronounce it cannot be issued a marriage certificate. Meanwhile, in Indonesia, pronouncing taklik talak is optional as regulated in the Compilation of Islamic Law and supported by a fatwa from the Indonesian Ulema Council (MUI), because the substance of protection for wives' rights is included in the Marriage and Religious Courts Law. In conclusion, although both legal systems recognize taklik talak as a marital agreement, Kedah considers it a formal obligation, while Indonesia considers it a non-binding option. These differences demonstrate the legal adaptations to the social needs and legal structures of each country, while remaining focused on protecting the wife's rights within the household.